2016
DOI: 10.1002/2016ms000635
|View full text |Cite
|
Sign up to set email alerts
|

The influence of model resolution on the simulated sensitivity of North Atlantic tropical cyclone maximum intensity to sea surface temperature

Abstract: Global climate models (GCMs) are routinely relied upon to study the possible impacts of climate change on a wide range of meteorological phenomena, including tropical cyclones (TCs). Previous studies addressed whether GCMs are capable of reproducing observed TC frequency and intensity distributions. This research builds upon earlier studies by examining how well GCMs capture the physically relevant relationship between TC intensity and SST. Specifically, the influence of model resolution on the ability of a GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Ng and Chan (2012) found that the interannual variation of TC activity over the BOB during October−December can be attributed to the variation in the atmospheric dynamic and thermodynamic conditions that are largely forced by ENSO's effect. Many model studies have been carried out recently in relation to TCs and SST over different ocean basins (e.g., Zhang et al, 2015Zhang et al, , 2019Strazzo et al, 2016). Zhang et al (2019) proposed that a strong association exists between tropical Atlantic SST and cyclone frequency over the ARB.…”
Section: Introductionmentioning
confidence: 99%
“…Ng and Chan (2012) found that the interannual variation of TC activity over the BOB during October−December can be attributed to the variation in the atmospheric dynamic and thermodynamic conditions that are largely forced by ENSO's effect. Many model studies have been carried out recently in relation to TCs and SST over different ocean basins (e.g., Zhang et al, 2015Zhang et al, , 2019Strazzo et al, 2016). Zhang et al (2019) proposed that a strong association exists between tropical Atlantic SST and cyclone frequency over the ARB.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in high-performance computing technologies have enabled multi-decadal simulations at “TC permitting” resolutions of ~25 km or finer ( 29 , 30 ). Models of this class vary considerably in the realism of their simulated storms but some are able to produce category 5 storms with credible relationships between maximum wind speeds and minimum central pressures ( 31 33 ). Storm counts and track distributions also compare favorably with observations in some of the models.…”
Section: Changes In Maximum Wind Speeds Of Tc Permitting Climate Mode...mentioning
confidence: 99%
“…Increasing the understanding of the environmental factors affecting TCs is one of the most effective ways to improve the ability to forecast TC intensity. According to previous studies, the following environmental factors are considered favorable for TC intensification: small vertical wind shear [9,10], high low-level vorticity [9,11], high upper-level divergence [12,13], high sea surface temperature [14,15], high water vapor content of the troposphere [16,17], and large amounts of convective available potential energy [18,19].…”
Section: Introductionmentioning
confidence: 99%